Hired : six months undercover in low-wage Britain - Bloodworth, James, 1982- (London : Atlantic books, 2018)
"Cracking open Britain's divisions - immigrant/British, North/South, urban/rural, working class/middle class, leave/remain - journalist James Bloodworth spends six months living and working across Britain, taking on the country's worst jobs. He lives on the meagre proceeds and discovers the anxieties and hopes of those he encounters, including working-class British, young students striving to make ends meet, and Eastern European immigrants."--Publisher's description.
Rugeley -- Blackpool -- South Wales Valleys -- London -- Epilogue.
Includes bibliographical references and index.
Keywords: Income -- Great Britain; Income; Industry; Labour and labouring classes - Great Britain; Occupations -- Great Britain; Occupations; Wages -- Great Britain; Wages; Great Britain